Kajian Hukum Tentang Implementasi Corporate Social Responsibility di Kabupaten Gresik Untuk Mendukung Pembangunan Daerah - Rizki Ameliah* (Universitas Airlangga, 2020)
Based on data from the Central Java Provincial Statistics Agency, the Company in Gresik Regency until 2015 reached 603 companies. The high development in the industrial sector certainly creates a variety of positive and negative impacts that will affect community activities and the sustainability of environmental ecosystems around them. So that there appears a compensation given by the company to the affected local residents where this compensation for the company is interpreted as a form of CSR (Corporate Social Responsibility). Given how the planning of the CSR program and the implementation of CSR programs that have been planned by the company, whether it runs effectively and runs in accordance with the program that has been planned together with the Local Government to prosper the community in the company's environment in Gresik Regency, Java Province East. The formulation of the problem in this research is first how the policy of the Gresik District Government in the regulation of CSR in Gresik Regency and secondly how the implementation of CSR policies in Gresik Regency in the context of regional development. This research is a study that uses empirical or sociolegal legal methods. The conclusion of this study is that the regulation on CSR in the law Number 40 of 2007 concerning limited liability companies and law number 25 of 2007 concerning investments still needs to be clarified and adjusted to other laws and regulations, including the Environmental Law and with related international legal instruments, including ISO 26000. This is intended to eliminate bias in the sense and standard of implementing CSR. In addition, the business community can implement the SCR more optimally, so that the objectives of implementing CSR on social and environmental aspects can be more successful and bring benefits, both for the company, society, environment and country.